All-temperature barocaloric effects at pressure-induced phase transitions - Xueting Zhao; Zhao Zhang; Takanori Hattori; Jiantao Wang; Lingli Li; Yating Jia; Wanwu Li; Jianing Xue; Xiaoyan Fan; Ruiqi Song; Jinlong Zhu; Peitao Liu; et al. (Nature Communications)
Abstract Caloric effects, which underpin one solution to solid-state refrigeration technologies, usually occur in the vicinity of solid-state phase transitions with a limited refrigeration temperature span. Here, we introduce and realize an unprecedented concept ‒ all-temperature barocaloric effect, i.e., a remarkable barocaloric effect in KPF6 across an exceptionally wide temperature span, from 77.5 to 300 K and potentially down to 4 K, covering typical room temperature, liquid nitrogen, liquid hydrogen, and liquid helium refrigeration regions. The directly measured barocaloric adiabatic temperature change reaches 12 K at room temperature and 2.5 K at 77.5 K upon the release of a 250 MPa pressure. This effect is attributed to a persistent phase transition to a rhombohedral high-pressure phase, as evidenced by pressure-dependent neutron powder diffraction, Raman scattering analyses, and first-principles calculations. We depict the thermodynamic energy landscape to account for the structural instability. This unique all-temperature barocaloric effect presents a novel approach to highly applicable solid-state refrigeration technology, transcending the conventional multi-stage scenario.